2009
DOI: 10.2187/bss.23.43
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Assessment of RISK in Long-Term Manned Space Exploration-Cell Death Factors in Space Radiation and/or Microgravity: A Review-

Abstract: One major concern regarding long-term manned space missions is the effect of accumulative doses of space radiation (the mean daily dose is 0.2 ~ 1 mSv). Such missions will inevitably expose astronauts to significant doses, and thus are expected to increase the risks of radiation-related carcinogenicity, neurotoxicity, and lifespan changes. These effects occur by nuclear and cytosol dysfunction, mitochondrial damage, and particular changes in signal transduction or protein synthesis. In addition, microgravity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Free radicals generated from mitochondria could play a role in many kinds of cell death; i.e., apoptosis, necrosis, autophagy. ( 83 , 84 ) In our published paper that reported the relationship between ROS generated from mitochondria and apoptosis, ( 9 ) we showed an electron microscopic picture of mitophagy impacted by an alkaline condition, whereas MnSOD transfected cells seemed normal, as shown in Fig. 5 .…”
Section: How Sod Work To Remove Oxidative Stress In Mitochondriamentioning
confidence: 60%
See 1 more Smart Citation
“…Free radicals generated from mitochondria could play a role in many kinds of cell death; i.e., apoptosis, necrosis, autophagy. ( 83 , 84 ) In our published paper that reported the relationship between ROS generated from mitochondria and apoptosis, ( 9 ) we showed an electron microscopic picture of mitophagy impacted by an alkaline condition, whereas MnSOD transfected cells seemed normal, as shown in Fig. 5 .…”
Section: How Sod Work To Remove Oxidative Stress In Mitochondriamentioning
confidence: 60%
“…( 82 ) Free radicals generated from mitochondria could play roles in any kind of cell death; i.e., apoptosis, necrosis and autophagy. ( 83 , 84 )…”
Section: Mitochondria-localized Manganese Superoxide Dismutase (Mnsodmentioning
confidence: 99%
“…Mitochondria control not only apoptosis but also necrosis and autophagy19. It has been reported that electron leakage (2–3%) from the mitochondrial electron transport chain and the reaction of these electrons with oxygen results in the generation of superoxides, which initiate oxidative stress2021.…”
mentioning
confidence: 99%
“…In addition, the mitochondrial generation of reactive oxygen species (ROS) relates to the aging process22. Thus, exposure to space environments, which are characterized by space radiation and microgravity, may increase mitochondria-related oxidative stress and subsequent cell death19.…”
mentioning
confidence: 99%
“…The biological effects of long-term, low-dose exposure to space radiation, including intracellular DNA and mitochondrial damage, may increase the risk of developing a number of disorders. ( 2 , 3 ) Such radiation effects are important factors to be considered in planning extended manned space missions. ( 3 5 ) Similarly, microgravity may influence cellular metabolism and function, including gene expression and signal transduction, and may result in cell death.…”
Section: Introductionmentioning
confidence: 99%